Herding in style allocations - Andreu, Laura; Ortiz, Cristina; Sarto, José Luis (Journal of Business Economics and Management, 2015)
The study examines herding behavior in the strategic allocations of UK pension plans. The results show that UK pension managers are involved in cross-sectional herd behavior. The study also examines herding from a quantitative perspective considering the number of managers changing their style allocations and from an intertemporal perspec- tive to examine the tendency of UK pension plans to imitate others over time. Finally, a robustness analysis considering passive style portfolios is applied to eliminate artificial herding. Hence, the paper contributes to the literature by analyzing herding at strategic allocations instead of at the individual stock level as well as by improving the methodol- ogy used to capture the herding phenomenon. The results have practical implications to design managers’ compensation schemes due to their influence on manager behavior.